Management of Educational Institutions in Realizing Inclusive Schools Model (Case Study of Inclusive Schools in Ponorogo) - Heriyudanta, Muhammad; Werdiningsih, Wilis (QUALITY, 2025)
This research aims to examine institutional management and inclusive school learning processes in Ponorogo. The study uses a qualitative approach with a case study design. The researchers are the key instrument. The research locations are SDN Negeri 4 Krebet and SD Immersion. The results of this study show that the learning processes at SDN 4 Krebet and SD Immersion are similar. The only difference is in the developmental aspect. The first step in admitting new students is to conduct an initial screening and evaluation to identify students with special needs. Due to the presence of ABK students, the curriculum has been adjusted. Both schools have individual learning programs (PPI) to provide unique learning opportunities for ABK students. Second, regarding institutional management, both principals agree that schools must prepare several aspects to organize inclusive schools: including the curriculum, human resources, and supporting facilities and infrastructure.